Safety Performance of Qwen2.5 Across Multi-Turn Multimodal Dialogues on MTMCS-Bench - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: How does the safety performance of Qwen2.5 models vary across different turn lengths in multi-turn multimodal dialogues on MTMCS-Bench compared to prior versions. 12 claims were extracted from source literature; 8 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.3/10. This report is a machine-generated literature sy
Machine-generated literature synthesis.